PENGARUH FASILITAS DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN KAPAL PELNI DI KOTA BATAM - Tutoq, yulita; Syaifullah, Syaifullah (LPPM Universitas Putera Batam, 2021)
In the most important vehicle service needs and this can be felt by the universe. In this study the goal is to be able to find out the causes of facilities and service quality on purchasing decisions, as well as knowing the facilities and service quality together can influence consumer purchasing decisions on Pelni ships. And in this research also uses descriptive research and quantitative approaches. And in the data collection technique using questionnaires. Meanwhile, sampling using non probability sampling technique with incidental sampling type. From the results of this study indicate that there is no effect of facilities on purchasing decisions, because the test results obtained tcount <ttable, tcount is 1.674 with a significance level of 0.097, while ttable is 1.984. While the influence of service quality on purchasing decisions, because in the test results show tcount> ttable with the calculation of the tcount value of 4.464 with a significance level of 0.000, with a value of t table of 1.984. And there is also, that there is an effect of facilities and service quality together on purchasing decisions, with the test results of the value of fcount is 10.629 with a significance level of 0.000, with a value of ftable of 2.465.